Defamation in the Digital Age: An Analysis of the Application of Restorative Justice under Indonesian Criminal Law - Emaliawati, Emaliawati (Yayasan Studi Cendekia Indonesia (YSCI), 2024)
The development of human civilisation is greatly influenced by advances in the field of communication and information, particularly through digitalisation. The negative impact of the freedom to access information and communication technology is also evident in the increasing number of cases of law violations through electronic media, including defamation. This research aims to examine how Indonesian criminal law handles defamation cases in the digital era, as well as the potential application of restorative justice in this context. The research questions include: how Indonesian criminal law handles defamation cases in the digital era; whether restorative justice can be applied in defamation cases, and how it is applied according to Indonesian criminal law; and how criminal liability for perpetrators of defamation in the digital era. The research method used is normative analysis through document studies and primary, secondary, and tertiary legal literature. The results of the research highlight the importance of understanding the criminal liability of defamation offenders under Indonesian criminal law. This research also explores the concept and application of restorative justice in defamation cases in the digital era, as well as its implications for the Indonesian criminal law framework.